2019
DOI: 10.1158/1055-9965.epi-18-0833
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Analysis of Common Copy Number Variation and Epithelial Ovarian Cancer Risk

Abstract: Background: Germline DNA copy number variation (CNV) is a ubiquitous source of genetic variation and remains largely unexplored in association with epithelial ovarian cancer (EOC) risk.Methods: CNV was quantified in the DNA of approximately 3,500 cases and controls genotyped with the Illumina 610k and HumanOmni2.5M arrays. We performed a genome-wide association study of common (>1%) CNV regions (CNVRs) with EOC and high-grade serous (HGSOC) risk and, using The Cancer Genome Atlas (TCGA), performed in silico an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 63 publications
2
24
0
Order By: Relevance
“…These mutations were shown to disrupt the RAD51C mRNA splicing and are considered to be likely pathogenic variants [20,98]. Large mutations were not included in risk estimates, however, it is suggested that they may contribute to familial breast/ovarian cancer risk [99,100]. As mentioned in the Results section, large mutations constitute a substantial fraction of all reported mutations, especially in the RAD51C and RAD51D genes; therefore, they may also influence the risk of OC.…”
Section: Discussionmentioning
confidence: 99%
“…These mutations were shown to disrupt the RAD51C mRNA splicing and are considered to be likely pathogenic variants [20,98]. Large mutations were not included in risk estimates, however, it is suggested that they may contribute to familial breast/ovarian cancer risk [99,100]. As mentioned in the Results section, large mutations constitute a substantial fraction of all reported mutations, especially in the RAD51C and RAD51D genes; therefore, they may also influence the risk of OC.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the severity of response to SARS-CoV-2 infection had a small, but significant, portion that was predictable from UK Biobank chromosomal-scale length variation [23]. Another group used a GWAS-type analysis employing logistic regression with copy number variation data collected from about 1800 ovarian cancer cases and 1800 controls to demonstrate that some germ line DNA copy number variations occur more frequently in women who develop epithelial ovarian cancer than in those who do not develop that form of cancer [24].…”
Section: Resultsmentioning
confidence: 99%
“…CNVs for NSCLC distinguished lung cancer from normal lung tissues, can be a prognostic indicator [46]. A number of low-to-common frequency CNVs might in uence the risk of epithelial ovarian cancer and tumor-gene expression [47]. DNA copy number losses in basal-like breast cancers were associated with signi cantly increased genomic instability and poor patient survival [48].…”
Section: Discussionmentioning
confidence: 99%